Outflowing Gas in the Planetary Nebula K 3-54 - Xiuhui Chen; Dejian Liu; Ping Yan; Binggang Ju; Dengrong Lu; Yingjie Li (The Astronomical Journal)
As planetary nebulae evolve, they develop slow and strong dust-driven stellar winds, making the joint study of dust and gas essential for understanding their nature. As a pilot investigation, we selected planetary nebula (PN) K 3-54 as our target, the only known PN in the Milky Way to exhibit infrared emission from both graphene (C _24 ) and fullerene (C _60 ). The gas is traced via molecular line emissions from ^12 CO, ^13 CO, and C ^18 O ( J  = 1 → 0), observed using the 13.7 m telescope of the Purple Mountain Observatory. We investigate the dynamics of this PN and identify a bipolar outflow. Preliminary results suggest that the large dynamical timescale of the outflow and the weak shock environment may account for the simultaneous survival of C _24 and C _60 within and around PN K 3-54.